Multifunctional composite fabric with wave absorption, flame retardation and ultraviolet absorption and preparation method thereof
Patent Information
- Application Number
- CN202610903389.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-09-04
- Estimated Expiration
- 2046-06-23
AI Technical Summary
[0013]In terms of material design and resource utilization, this invention abandons the traditional approach of relying on high proportions of single-functional fillers or additives. Instead, it creates a core-shell structured composite microwave absorber, Fe3O4@TiO2@PANI, possessing both electromagnetic loss and UV absorption properties. This absorber is then composited with an intrinsically flame-retardant poly(ethylene phosphate-hydroxyethyl acrylate-styrene) copolymer (PVHS) matrix and loaded onto a high-temperature resistant flame-retardant fiber fabric. With low filler content, it achieves an intrinsic integration of three functions: efficient electromagnetic wave absorption, excellent flame retardancy, and long-lasting UV aging resistance. This fundamentally solves the key problems of high filler content damaging matrix performance and hindering functional synergy. The underlying process system—"controllable synthesis of core-shell structure - intrinsic flame-retardant polymerization - low-content uniform blending/molding"—is stable and controllable, ensuring the performance is achieved. The composite fabric can meet the requirements of cutting-edge fields demanding electromagnetic stealth, fire safety, and extreme outdoor durability, and can be directly applied to next-generation camouflage and protective equipment, special industry workwear, flexible interiors for aerospace vehicles, and high-end outdoor equipment. Its core technological barrier lies in the material creation concept of "intrinsic multifunctional synergistic design of structure/components - low load and high efficiency composite", which breaks through the bottleneck of high addition amount, single function or simple superposition in traditional technology, and forms an advanced material system and solution that combines lightweight, flexibility, strength and toughness and environmental resistance.
Smart Images

Figure CN122428507B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional composite materials technology, specifically relating to a multifunctional composite fabric with electromagnetic wave absorption, flame retardancy and ultraviolet absorption functions, and its preparation method. Background Technology
[0002] With the rapid development of electronic information technology, electromagnetic waves are widely used in communication, radar, detection, and various electronic devices. The resulting electromagnetic radiation pollution has become a prominent problem affecting human health and the normal operation of equipment. Electromagnetic wave absorbing materials can convert the energy of incident electromagnetic waves into heat or other forms of energy dissipation, making them an effective means of fundamentally controlling electromagnetic pollution. Among the many types of absorbing materials, absorbing coatings have attracted much attention in the fields of stealth and civilian protection due to their advantages such as flexible formulation design, simple construction, and applicability to complex curved surfaces.
[0003] In existing technologies, electromagnetic wave absorption is achieved by adding microwave-absorbing fillers to coatings. Summary of the Invention
[0004] In this invention, through intrinsic material design and structural control, a synergistic technology is unexpectedly obtained that integrates multiple functions such as wave absorption, flame retardancy, and UV resistance into a fabric substrate with low filler addition.
[0005] In particular, one aspect of the present invention aims to achieve integrated performance of high-efficiency electromagnetic wave absorption, excellent flame retardancy and long-lasting UV aging resistance on a fabric substrate through intrinsic material design and structural control with low filler addition.
[0006] One aspect of the present invention relates to a composition for preparing a multifunctional composite fabric, comprising: a composite microwave absorber and a polymer matrix, said composite microwave absorber comprising a Fe3O4@TiO2@polyaniline composite having a Fe3O4 core, a TiO2 layer coating the Fe3O4 core, and polyaniline on the TiO2 layer, wherein the mass ratio of aniline to Fe3O4@TiO2 is 1:5 to 10:1, said polymer matrix comprising poly(ethylene phosphate-hydroxyethyl acrylate-styrene), wherein the molar ratio of vinyl phosphate, hydroxyethyl acrylate, and styrene is 1 to 15:7:1, and based on the total weight of the Fe3O4@TiO2@polyaniline composite and the poly(ethylene phosphate-hydroxyethyl acrylate-styrene) matrix, the mass fraction of the Fe3O4@TiO2@polyaniline composite is 0.1 to 20% by weight, and the mass fraction of the poly(ethylene phosphate-hydroxyethyl acrylate-styrene) matrix is 80 to 99.9% by weight. In this invention, the terms "composition" and "composite slurry" are used interchangeably.
[0007] Another aspect of the invention relates to a method for preparing a composition for manufacturing multifunctional composite fabrics, comprising: providing a Fe3O4@TiO2@polyaniline composite and poly(ethylene phosphate-hydroxyethyl acrylate-styrene), and contacting the Fe3O4@TiO2@polyaniline composite with the poly(ethylene phosphate-hydroxyethyl acrylate-styrene). Preferably, the mixture comprising the Fe3O4@TiO2@polyaniline composite and the poly(ethylene phosphate-hydroxyethyl acrylate-styrene) copolymer is ultrasonically stirred at room temperature for 20-50 min.
[0008] Another aspect of the invention relates to a multifunctional composite fabric comprising: a base fabric; and the above-described composition applied to said base fabric. Preferably, the base fabric is a high-temperature resistant, flame-retardant fiber fabric. For example, the base fabric is one or more selected from polyacrylonitrile pre-oxidized filaments, phenolic fibers, polyphenylene sulfide fibers, polyimide fibers, or aramid fibers. In this invention, the terms "base fabric" and "substrate" are used interchangeably.
[0009] Another aspect of the invention relates to a method for preparing a multifunctional composite fabric, comprising: preparing a base fabric; and applying the above-described composition onto the base fabric by means of a multiple impregnation or pad-dyeing process. Preferably, the mass ratio of the coating formed by the composition to the base fabric is 0.5 to 1.5:1.
[0010] Another aspect of the invention relates to protective equipment comprising the above-described composition or the above-described multifunctional composite fabric. Preferably, the protective equipment is outdoor special protective equipment, stealth material, or personal protective equipment for complex electromagnetic environments.
[0011] Another aspect of the invention relates to electromagnetic shielding, flame retardant, or weather-resistant functional components comprising the above-described compositions.
[0012] Compared with the prior art, the present invention achieves at least one of the following beneficial effects:
[0013] In terms of material design and resource utilization, this invention abandons the traditional approach of relying on high proportions of single-functional fillers or additives. Instead, it creates a core-shell structured composite microwave absorber, Fe3O4@TiO2@PANI, possessing both electromagnetic loss and UV absorption properties. This absorber is then composited with an intrinsically flame-retardant poly(ethylene phosphate-hydroxyethyl acrylate-styrene) copolymer (PVHS) matrix and loaded onto a high-temperature resistant flame-retardant fiber fabric. With low filler content, it achieves an intrinsic integration of three functions: efficient electromagnetic wave absorption, excellent flame retardancy, and long-lasting UV aging resistance. This fundamentally solves the key problems of high filler content damaging matrix performance and hindering functional synergy. The underlying process system—"controllable synthesis of core-shell structure - intrinsic flame-retardant polymerization - low-content uniform blending / molding"—is stable and controllable, ensuring the performance is achieved. The composite fabric can meet the requirements of cutting-edge fields demanding electromagnetic stealth, fire safety, and extreme outdoor durability, and can be directly applied to next-generation camouflage and protective equipment, special industry workwear, flexible interiors for aerospace vehicles, and high-end outdoor equipment. Its core technological barrier lies in the material creation concept of "intrinsic multifunctional synergistic design of structure / components - low load and high efficiency composite", which breaks through the bottleneck of high addition amount, single function or simple superposition in traditional technology, and forms an advanced material system and solution that combines lightweight, flexibility, strength and toughness and environmental resistance.
[0014] Compared with the solution of this invention, existing microwave absorbing materials have limited functionality and struggle to simultaneously achieve flame retardancy and UV aging resistance. Furthermore, traditional processes suffer from technical bottlenecks due to the high filler content, which severely compromises the flexibility and processability of the substrate. Specifically, existing technologies exhibit at least one of the following shortcomings:
[0015] 1) Current research on microwave absorbing coatings mostly focuses on improving their electromagnetic loss performance, such as reducing thickness, broadening the frequency band, and increasing absorption intensity, while insufficient attention is paid to the multifunctional adaptability required by materials in complex real-world environments. For example, microwave absorbing coatings exposed to outdoor environments for extended periods are highly susceptible to aging, chalking, or degradation due to ultraviolet radiation from sunlight, leading to a significant decrease in microwave absorption performance or even failure. In many applications, such as special protective clothing, tarpaulins, and aerospace interior materials, flame retardancy and safety are indispensable key performance characteristics.
[0016] 2) Achieving the flame-retardant function of microwave absorbing materials often relies on the physical addition of flame retardants. This method often damages the mechanical properties of the matrix, processing fluidity, and dispersibility of the microwave absorbing filler due to the high amount of additives, making it difficult to achieve a balanced and unified performance of high-efficiency microwave absorption, long-lasting flame retardancy, and aging resistance.
[0017] In contrast, intrinsic flame-retardant polymers achieve flame-retardant functionality at the molecular level by introducing flame-retardant elements such as phosphorus, nitrogen, and silicon into the polymer backbone or side chains via covalent bonds. These materials typically possess potential advantages such as high flame-retardant efficiency, long-lasting effect, good migration resistance, and minimal impact on the original properties of the matrix.
[0018] The preparation method provided by this invention has good application prospects because it is simple in process, requires less equipment, and has a large output. Attached Figure Description
[0019] Figure 1 This is a schematic diagram illustrating the synthesis of the polymer matrix obtained in an embodiment of the present invention;
[0020] Figure 2 The above is the 1H NMR spectrum of the polymer matrix prepared in an embodiment of the present invention.
[0021] Figure 3 The cross-sectional microstructure, surface microstructure, and physical image of the multifunctional composite material obtained in Example 1 of this invention are shown.
[0022] Figure 4 The limiting oxygen index diagram is shown for the multifunctional composite slurry prepared according to the embodiments of the present invention, where FTP@PVHS-2, FTP@PVHS-4, FTP@PVHS-6 and FTP@PVHS-8 represent FTP mass fractions of 2 wt%, 4 wt%, 6 wt%, and 8 wt%, respectively.
[0023] Figure 5 Here is a scanning electron microscope image of the multifunctional polyacrylonitrile pre-oxidized fiber composite fabric prepared in Example 4 of this invention;
[0024] Figure 6 Three-dimensional reflection loss diagrams of the multifunctional polyacrylonitrile pre-oxidized filament composite fabrics obtained in Examples 4 to 6 of this invention;
[0025] Figure 7 The heat release rate diagrams are for pure polyacrylonitrile pre-oxidized filament (POF) and the multifunctional polyacrylonitrile pre-oxidized filament composite fabric (FTP@PVHS / POF) prepared in Example 6 of this invention.
[0026] Figure 8 This is a limiting oxygen index diagram of the pure nonwoven fabric prepared in Example 9 of the present invention and the fabric coated with a multifunctional composite slurry. 2, 3, and 4 represent the mass ratios of FTP@PVHS to the base fabric as 0.5:1, 1:1, and 1.5:1, respectively. Detailed Implementation
[0027] This invention provides an innovative solution by designing and preparing a core-shell structured Fe3O4@TiO2@polyaniline composite microwave absorber, which possesses both excellent electromagnetic wave absorption performance and intrinsically strong ultraviolet absorption characteristics. Simultaneously, an intrinsically flame-retardant poly(ethylene phosphate-hydroxyethyl acrylate-styrene) copolymer is innovatively synthesized as the coating matrix. The phosphate ester structural units contained therein are covalently bonded to the polymer backbone, avoiding problems such as poor interfacial compatibility, flame retardant migration, and damage to the mechanical properties of the matrix that may occur with traditional physical additive methods. Furthermore, high-temperature flame-retardant fibers, such as pre-oxidized polyacrylonitrile filaments and phenolic fibers, which possess excellent properties including high-temperature resistance, non-flammability, textile processability, and chemical structural stability, are selected as the fabric substrate. Through a low-filler-ratio physical blending and impregnation process, a multifunctional composite fabric integrating high-efficiency microwave absorption, excellent flame retardancy, and UV aging resistance is successfully prepared.
[0028] More specifically, the present invention relates to the following technical solutions:
[0029] This invention provides a method for preparing a multifunctional composite fiber fabric that combines electromagnetic wave absorption, flame retardancy, and ultraviolet absorption functions, comprising the following steps:
[0030] (1) Preparation of Fe3O4@TiO2@polyaniline composite microwave absorber (FTP)
[0031] First, Fe3O4 was dispersed in a mixed solution of ethanol and water, stirred and sonicated. Then, a silane coupling agent was slowly added dropwise to the Fe3O4 dispersion, heated and stirred, and then washed and dried to obtain silane coupling agent modified Fe3O4, denoted as K-Fe3O4.
[0032] K-Fe3O4 and titanate were mixed and ultrasonicated, then slowly added dropwise to a mixture of ethanol and water while stirring. The mixture was separated by magnetic separation and transferred to a polytetrafluoroethylene reactor, where ethanol and deionized water were added for further reaction. After washing and drying, a core-shell structured product, denoted as Fe3O4@TiO2, was obtained.
[0033] Fe3O4@TiO2 was mixed with perchloric acid and sonicated, then transferred to a low-temperature constant-temperature water bath. Aniline monomer was slowly added dropwise under mechanical stirring until homogeneous. Ammonium persulfate was then slowly added dropwise while continuously stirring. After washing and freeze-drying, a dark green product, namely the Fe3O4@TiO2@polyaniline composite microwave absorber, was finally obtained.
[0034] (2) Preparation of poly(ethylene phosphate-hydroxyethyl acrylate-styrene) matrix (PVHS)
[0035] Accurately weighed amounts of hydroxyethyl acrylate (HEA), ethylene phosphate (VPA), styrene (SM), and the initiator azobisisobutyramidine hydrochloride (AIBA) were placed in a 100 mL reaction flask. A mixture of ethanol and water was then added to the flask, and the mixture was stirred. Nitrogen gas was continuously bubbled into the flask, and the temperature was increased under a nitrogen atmosphere, with the reaction time controlled to ensure complete reaction. The reactants were then purified using the hexane precipitation method, and the polymer matrix PVHS was obtained by centrifugation.
[0036] (3) Preparation of composite slurry
[0037] The FTP functional filler and PVHS coating matrix were weighed at a precise mass ratio and added to a round-bottom flask. The mixture was ultrasonically stirred at room temperature to obtain a uniformly dispersed FTP / PVHS composite microwave absorbing slurry.
[0038] (4) Preparation of composite fabrics
[0039] The composite microwave absorbing paste is dispersed in a solvent to form a composite coating; the high-temperature resistant and flame-retardant fiber fabric is impregnated in the composite coating, and after drying and curing, the multifunctional composite fabric is obtained.
[0040] Preferably, in step (1), the silane coupling agent is selected from one or more of aminosilane coupling agents, epoxysilane coupling agents, and mercaptosilane coupling agents.
[0041] Preferably, in step (1), the titanate is selected from one or more of tetramethyl titanate, tetraethyl titanate, tetraisopropyl titanate, and tetrabutyl titanate, and is preferably tetrabutyl titanate.
[0042] Preferably, in step (1), the ultrasonic treatment time of Fe3O4 in a mixed solution of ethanol and water is 10-30 min.
[0043] Preferably, in step (1), after the silane coupling agent is added dropwise to the Fe3O4 dispersion, the heating temperature is 60-80℃ and the stirring time is 2-4 h.
[0044] Preferably, in step (1), the ultrasonic treatment time for the K-Fe3O4 and titanate mixture is 10-30 min.
[0045] Preferably, in step (1), after the K-Fe3O4 and titanate mixture is added dropwise to the mixture of ethanol and water, the stirring time is 0.5-2 h.
[0046] Preferably, in step (1), the reaction temperature of the polytetrafluoroethylene reactor is 180-230℃ and the reaction time is 8-14 h.
[0047] Preferably, in step (1), the ultrasonic treatment time after mixing Fe3O4@TiO2 with perchloric acid is 5-15 min.
[0048] Preferably, in step (1), the in-situ polymerization reaction is carried out in an acidic aqueous solution, and the mass ratio of aniline monomer to Fe3O4@TiO2 is (1~4):1.
[0049] Preferably, in step (1), the temperature of the low-temperature constant temperature water bath is set to 0-5℃.
[0050] Preferably, in step (1), after adding ammonium persulfate, the stirring time is 6-15 h.
[0051] Preferably, in step (2), nitrogen gas is continuously introduced for 20-40 minutes, and the temperature is raised to 60-70°C in a nitrogen atmosphere.
[0052] Preferably, in step (2), the reaction time under a nitrogen atmosphere is controlled to be 45-50 h.
[0053] Preferably, in step (2), the molar ratio of vinyl phosphate, hydroxyethyl acrylate and styrene is (6.5~7):7:1.
[0054] Preferably, in step (3), the mass fraction of the functional filler in the coating matrix is 2% to 8%.
[0055] Preferably, in step (3), the mixing system is ultrasonically stirred at room temperature for 20-50 min.
[0056] Preferably, in step (4), the high-temperature resistant flame-retardant fiber fabric is one or more of polyacrylonitrile pre-oxidized filament, phenolic fiber, polyphenylene sulfide fiber, polyimide fiber or aramid fiber.
[0057] Preferably, in step (4), a multiple immersion or pad dyeing process is used, and the mass ratio of the coating formed by the multifunctional composite material to the fabric substrate is (0.5~1.5):1.
[0058] Preferably, in step (4), the drying and curing temperature is 60-80℃ and the processing time is 24-60 h.
[0059] In one embodiment of the invention, based on the total weight of the Fe3O4@TiO2@polyaniline composite and the poly(ethylene phosphate-hydroxyethyl acrylate-styrene) matrix, the mass fraction (or amount used) of the Fe3O4@TiO2@polyaniline composite is 0.1 to 20 wt%, more preferably 2 to 8 wt%. In one embodiment, the mass fraction (or amount used) of the Fe3O4@TiO2@polyaniline composite is 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, or 19 wt%, more preferably 4 wt%. The above proportions remain applicable during the preparation or use of the composition or composite slurry.
[0060] In this invention, the mass fraction of functional filler (FTP) in the coating matrix (PVHS) is a key parameter affecting the final composite material's electromagnetic, mechanical, and processability properties. Extensive preliminary exploratory experiments revealed that when the FTP mass fraction is below 2%, its content in the matrix is insufficient to form an effective conductive / dielectric network, resulting in weak electromagnetic wave absorption performance of the composite material (optimal performance cannot be achieved, but one of the objectives of this invention is still accomplished). When the FTP mass fraction is above 8%, excessive filler significantly affects the film-forming properties and flexibility of the PVHS matrix, and is prone to agglomeration leading to uneven dispersion, potentially reducing the uniformity and stability of performance (optimal performance cannot be achieved, but one of the objectives of this invention is still accomplished). Therefore, considering both performance and processability, the preferred mass fraction range for FTP is 2% to 8%. Within this range, the filler can fulfill its function while maintaining good processability of the matrix. The following examples will primarily use 4% as a representative to demonstrate the excellent effects within this preferred range.
[0061] In one embodiment of the invention, based on the total weight of the Fe3O4@TiO2@polyaniline composite and the poly(ethylene phosphate-hydroxyethyl acrylate-styrene) matrix, the mass fraction (or amount used) of the poly(ethylene phosphate-hydroxyethyl acrylate-styrene) matrix is 80 to 99.9% by weight, more preferably 92 to 98% by weight. In one embodiment, the mass fraction (or amount used) of the poly(ethylene phosphate-hydroxyethyl acrylate-styrene) matrix is 81% by weight, 82% by weight, 83% by weight, 84% by weight, 85% by weight, 86% by weight, 87% by weight, 88% by weight, 89% by weight, 90% by weight, 91% by weight, 92% by weight, 93% by weight, 94% by weight, 95% by weight, 96% by weight, 97% by weight, 98% by weight, 98.5% by weight, 99% by weight, or 9.5% by weight. More preferably, it is 96% by weight. The above proportions still apply in the preparation or use of the composition or composite slurry.
[0062] In one embodiment of the present invention, in the Fe3O4@TiO2@polyaniline composite, the mass ratio of aniline to Fe3O4@TiO2 is 1:5 to 10:1, more preferably 1:1 to 4:1. In one embodiment, this ratio is 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, or 9:1. The above ratios remain applicable in the preparation or use of the Fe3O4@TiO2@polyaniline composite.
[0063] In one embodiment of the present invention, the molar ratio of vinyl phosphate, hydroxyethyl acrylate and styrene in the poly(vinyl phosphate-hydroxyethyl acrylate-styrene) matrix is 1 to 15:7:1, more preferably 6.5 to 7:7:1. In one implementation, the ratio is, for example, 1.5:7:1, 2:7:1, 2.5:7:1, 3:7:1, 3.5:7:1, 4:7:1, 4.5:7:1, 5:7:1, 5.5:7:1, 6:7:1, 6.5:7:1, 7:7:1, 7.5:7:1, 8:7:1, 8.5:7:1, 9:7:1, 9.5:7:1, 10:7:1, 10.5:7:1, 11:7:1, 11.5:7:1, 12:7:1, 12.5:7:1, 13:7:1, 13.5:7:1, 14:7:1, and 14.5:7:1. The above ratios remain applicable in the preparation or use of the poly(ethylene phosphate-hydroxyethyl acrylate-styrene) matrix.
[0064] In one embodiment of the invention, the mass ratio of the coating formed by the composite slurry to the fabric substrate is 0.5:1 to 1.5:1. It can also be 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, or 1.4:1. In this application, the "mass ratio" refers to the mass ratio of the coating to the substrate (fabric) in the final multifunctional composite fabric, preferably in the multifunctional composite fabric after drying.
[0065] The composite fabric prepared by the method described in this invention has the characteristics of flexibility, lightweight and multifunctionality, and can be widely used in fields with stringent requirements for comprehensive performance, such as outdoor special protective equipment, stealth tarpaulins, aerospace interiors and personal protection in complex electromagnetic environments.
[0066] To enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0067] Preparation Example 1
[0068] The Fe3O4@TiO2@polyaniline composite microwave absorber was prepared by the following method:
[0069] Fe3O4 (Fe3O4 / ~300 nm, 10 g, 43.1 mmol) was dispersed in a solution of ethanol (AR, 300 mL) and water (50 mL), stirred, and sonicated for 30 min. 30.29 mL (129.3 mmol) of KH-550 (3-aminopropyltriethoxysilane / AR) was slowly added dropwise to the Fe3O4 dispersion, and the mixture was stirred at 70 °C for 3 h. The mixture was separated by magnetic separation and washed alternately with ethanol / deionized water. Finally, the product was dried in a 60 °C oven to obtain KH-550 modified Fe3O4, denoted as K-Fe3O4. K-Fe3O4 (5 g) and tetrabutyl titanate (AR, 10 g, 29.41 mmol) were mixed and sonicated for 30 min. A mixture of ethanol (60 mL) and water (30 mL) was slowly added dropwise at 40 °C, and the mixture was stirred for 1 h. The product was separated by magnetic separation and transferred to a polytetrafluoroethylene reactor. Ethanol (40 mL) and deionized water (20 mL) were added, and the reaction was carried out at 200 °C for 12 h. Finally, the product was separated by magnetic separation and washed with alternating ethanol / deionized water. The product was then dried in a 60 °C oven to obtain a core-shell structured product, Fe3O4@TiO2. Fe3O4@TiO2 (0.2 g) was mixed with 1 mol / L perchloric acid (AR, 200 mL) and sonicated for 10 min, then transferred to a 0 °C constant temperature water bath. Under mechanical stirring, 0.2 g, 0.4 g, 0.6 g, and 0.8 g of aniline monomer (AR) were slowly added dropwise, and mixed for 30 min until homogeneous. Then, ammonium persulfate (AR, 2.617 g) was slowly added dropwise, and the mixture was stirred continuously at 0 °C for 12 h. After magnetic separation and alternating washing with ethanol / deionized water, the product was freeze-dried for 2 days to obtain a dark green product. Based on the mass ratio of aniline monomer to Fe3O4@TiO2, the samples were named Fe3O4@TiO2@PANI-1, Fe3O4@TiO2@PANI-2, Fe3O4@TiO2@PANI-3 and Fe3O4@TiO2@PANI-4, respectively.
[0070] Preparation Example 2
[0071] Poly(ethylene phosphate-hydroxyethyl acrylate-styrene) copolymer is prepared by the following method:
[0072] Accurately weighed amounts of hydroxyethyl acrylate (99%, HEA), ethylene phosphoric acid (>95%, VPA), styrene (99%, SM), and the initiator azobisisobutyramidine hydrochloride (AIBA / 97%, 0.078 g) were placed in a 100 mL reaction flask. A mixed solvent consisting of deionized water (23.8 mL) and ethanol (12.93 mL) was then added to the flask, and the mixture was stirred at room temperature until all components were uniformly dispersed. Nitrogen gas was bubbled into the flask for 30 minutes, and the temperature was raised to 65°C under a nitrogen atmosphere and the reaction was continued for 48 hours to ensure complete reaction. The reactants were then purified by hexane (97%) precipitation, and the polymer was obtained by centrifugation. Based on different combinations of monomers, the synthesized polymers were named PVHS, PVH, PVS, and PHS, respectively, with PVHS being the most favorable result.
[0073] Example 1
[0074] A method for preparing a multifunctional composite material with electromagnetic wave absorption, flame retardancy, and ultraviolet absorption functions includes the following steps:
[0075] Step 1: Material Selection
[0076] 4 parts of Fe3O4@TiO2@polyaniline composite microwave absorber;
[0077] 96 parts of poly(ethylene phosphate-hydroxyethyl acrylate-styrene) copolymer;
[0078] 50 parts of deionized water.
[0079] Step 2: Prepare slurry
[0080] 96 parts of poly(ethylene phosphate-hydroxyethyl acrylate-styrene) copolymer were added to a reaction vessel, along with 50 parts of deionized water. The mixture was stirred at 400 r / min for 20 minutes. Four parts of Fe3O4@TiO2@polyaniline composite microwave absorber were added in portions, and the mixture was then ultrasonically stirred at room temperature for 30 minutes to ensure complete dispersion in the solution. The mixture was then filtered to obtain a mixed slurry.
[0081] Step 3: Molding
[0082] The mixed slurry was poured into a molding mold and dried at 60°C for 48 hours to cure and form a multifunctional composite material with a thickness of 1.0 mm.
[0083] Example 2
[0084] The difference from Example 1 is that in step 1, the Fe3O4@TiO2@polyaniline composite microwave absorber is 2 parts; and the poly(ethylene phosphate-hydroxyethyl acrylate-styrene) copolymer is 98 parts.
[0085] Example 3
[0086] The difference from Example 1 is that in step 1, the Fe3O4@TiO2@polyaniline composite microwave absorber is 8 parts; and the poly(ethylene phosphate-hydroxyethyl acrylate-styrene) copolymer is 92 parts.
[0087] Example 4
[0088] A method for preparing a multifunctional polyacrylonitrile pre-oxidized filament composite fabric with electromagnetic wave absorption, flame retardancy, and ultraviolet absorption functions includes the following steps:
[0089] Step 1: Material Selection
[0090] 4 parts of Fe3O4@TiO2@polyaniline composite microwave absorber;
[0091] 96 parts of poly(ethylene phosphate-hydroxyethyl acrylate-styrene) copolymer;
[0092] 50 parts deionized water;
[0093] 100 parts of pre-oxidized polyacrylonitrile filament fabric.
[0094] Step 2: Prepare slurry
[0095] 96 parts of poly(ethylene phosphate-hydroxyethyl acrylate-styrene) copolymer were added to a reaction vessel, along with 50 parts of deionized water. The mixture was stirred at 400 r / min for 20 minutes. Four parts of Fe3O4@TiO2@polyaniline composite microwave absorber were added in portions, and the mixture was then ultrasonically stirred at room temperature for 30 minutes to ensure complete dispersion in the solution. The mixture was then filtered to obtain a mixed slurry.
[0096] Step 3: Fabric Lamination
[0097] The pre-oxidized polyacrylonitrile filament fabric is immersed in the mixed slurry obtained in step 2, and the slurry is applied using a multiple immersion process.
[0098] Step 4: Drying and curing
[0099] The impregnated fabric was dried at 60°C for 24 hours to obtain a multifunctional composite fabric. The mass ratio of the composite coating to the fabric substrate was 0.5:1.
[0100] Example 5
[0101] The difference from Example 4 is that the mass ratio of the composite coating to the fabric substrate is 1:1, while the remaining steps and conditions are the same as in Example 4.
[0102] Example 6
[0103] The difference from Example 4 is that the mass ratio of the composite coating to the fabric substrate is 1.5:1, while the remaining steps and conditions are the same as in Example 4.
[0104] Example 7
[0105] The difference from Example 6 is that in step 1, the fabric substrate is replaced with a non-woven fabric.
[0106] Example 8
[0107] A method for preparing a comparative material to illustrate the performance differences between core-shell structured composite microwave absorbers and physically mixed fillers includes the following steps:
[0108] Step 1: Material Selection
[0109] Two parts of Fe3O4 powder;
[0110] Two parts of polyaniline powder;
[0111] 96 parts of poly(ethylene phosphate-hydroxyethyl acrylate-styrene) copolymer;
[0112] 50 parts deionized water;
[0113] Step 2: Prepare slurry
[0114] 96 parts of poly(ethylene phosphate-hydroxyethyl acrylate-styrene) copolymer were added to a reaction vessel, along with 50 parts of deionized water. The mixture was stirred at 400 r / min for 20 minutes. Two parts of Fe3O4 powder and two parts of polyaniline powder were added in portions, and the mixture was then ultrasonically stirred at room temperature for 30 minutes to disperse it in the solution. The mixture was then filtered to obtain a mixed slurry.
[0115] Step 3: Molding
[0116] The mixed slurry was poured into a molding mold and dried at 60°C for 48 hours to solidify, thus obtaining the comparative material.
[0117] Example 9
[0118] Raw, untreated nonwoven fabric.
[0119] Example 10
[0120] A comparative material preparation method, used to illustrate the effect of combining the FTP microwave absorber of the present invention with a commercially available additive flame retardant polymer matrix, includes the following steps:
[0121] Step 1: Material Selection
[0122] 4 parts of Fe3O4@TiO2@polyaniline composite microwave absorber;
[0123] 96 samples of commercially available water-based acrylic flame-retardant coatings;
[0124] 50 parts deionized water;
[0125] Step 2: Prepare slurry
[0126] 96 parts of commercially available water-based acrylic flame retardant coating were added to a reaction vessel, along with 50 parts of deionized water. The mixture was stirred at 400 r / min for 20 minutes. Four parts of Fe3O4@TiO2@polyaniline composite microwave absorber were added in portions, and the mixture was then ultrasonically stirred at room temperature for 30 minutes to disperse it in the solution. The mixture was then filtered to obtain a mixed slurry.
[0127] Step 3: Molding
[0128] The mixed slurry was poured into a molding mold and dried at 60°C for 48 hours to solidify, thus obtaining the comparative material.
[0129] Example 11
[0130] A method for preparing a comparative material, used to illustrate the effect of combining the FTP microwave absorber of the present invention with an intrinsic flame-retardant polymer matrix, includes the following steps:
[0131] Step 1: Material Selection
[0132] 4 parts of Fe3O4@TiO2@polyaniline composite microwave absorber;
[0133] 96 parts of polyphosphazene (PZS);
[0134] 50 parts deionized water;
[0135] Step 2: Prepare slurry
[0136] Add 96 parts of polyphosphazene (PZS) to a reaction vessel, add 50 parts of deionized water, and stir at 400 r / min for 20 minutes; add 4 parts of Fe3O4@TiO2@polyaniline composite microwave absorber in portions, and then ultrasonically stir at room temperature for 30 minutes to disperse it in the solution. Filter to obtain a mixed slurry.
[0137] Step 3: Molding
[0138] The mixed slurry was poured into a molding mold and dried at 60°C for 48 hours to solidify, thus obtaining the comparative material.
[0139] The samples obtained from the above embodiments and comparative examples were subjected to performance tests, and the results are shown in Table 1.
[0140] Table 1 Comparison of Performance Test Results
[0141]
[0142] Example 8 used the same intrinsic flame-retardant PVHS matrix (96 parts) and the same total functional filler addition (4 parts) as Example 1. The only difference was that the "core-shell structure Fe3O4@TiO2@PANI composite microwave absorber" of the present invention was replaced with a "simple physical mixture of Fe3O4 and polyaniline (PANI)". The results showed that, at the same test thickness, the microwave absorption performance and ultraviolet shielding efficiency of Example 8 were much lower than those of Example 1. This "controlled variable" comparison strongly proves that the superior performance of the present invention does not stem from the simple summation of the functions of each component, but is the result of the unique interfacial polarization effect caused by the core-shell structure, the electromagnetic synergy between components, and the structured ultraviolet absorption path, which cannot be achieved by simple physical mixing.
[0143] A comparison of Examples 1, 2, and 3 shows that the performance of the final composite material can be effectively controlled by adjusting the mass fraction (2%–8%) of the functional filler FTP in the PVHS matrix. For example, when the FTP content is 4% (Example 1), the microwave absorption performance is optimal (reflection loss -37.25 dB); when the FTP content is reduced to 2% (Example 2), the microwave absorption performance weakens somewhat, but the limiting oxygen index (LOI) remains at a high level of 39.3%; when the FTP content is increased to 8% (Example 3), the microwave absorption performance is comparable to that at 4%, but the LOI slightly decreases to 36.2%. This indicates that within the preferred range defined by this invention, both the electromagnetic function of FTP and the good flame-retardant properties of the PVHS matrix can be maintained, achieving a balance between functionality and processability.
[0144] A comparison of the performance data of Example 9 (original nonwoven fabric) with Example 7 shows that its limiting oxygen index is only 21.5%, and it has almost no electromagnetic wave absorption or ultraviolet protection properties. In stark contrast, even nonwoven fabric substrates that do not inherently possess flame-retardant properties, after being treated with the composite coating of this invention, have their limiting oxygen index significantly increased to over 30.0%, and are simultaneously endowed with excellent wave absorption properties and high ultraviolet shielding efficiency. This directly and powerfully demonstrates that the multifunctional composite coating prepared by this invention has a strong versatility enhancement effect on different substrates.
[0145] As can be seen from the comparison of Examples 4, 5, and 6, by adjusting the impregnation process to control the coating load (mass ratio from 0.5:1 to 1.5:1), the properties of the final composite fabric can be continuously and controllably adjusted. For example, both the microwave absorption and flame retardant properties increase with increasing coating load. This provides a flexible solution for the product of this invention in application scenarios with different protection levels, demonstrating the superiority of the process and its application adaptability.
[0146] Examples 10 and 11 respectively replaced the PVHS matrix of the present invention with commercially available additive flame-retardant coatings and other intrinsically flame-retardant polymers (PZS). The results showed that even with the same FTP microwave absorber and dosage, its microwave absorption performance, flame retardant performance, and UV shielding efficiency were all significantly lower than those of the PVHS matrix system of the present invention. This fully demonstrates that the specific molecular structure of PVHS (containing phosphate esters, hydroxyl groups, benzene rings, etc.) has unique advantages in terms of compatibility with FTP, interfacial interactions, and film-forming properties, and is key to achieving multifunctional integration with low dosage; it cannot be replaced by any flame-retardant matrix.
[0147] Finally, those skilled in the art should understand that the embodiments described in the specification and drawings are merely illustrative of the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. The technical solutions of the present invention have been fully disclosed through specific embodiments and can achieve the aforementioned technical effects. Any modifications or improvements derived from the technical features defined in the claims of the present invention through equivalent substitutions, conventional adjustments, or techniques known in the art, as long as they do not depart from the essential content of the technical solutions of the present invention, shall fall within the scope of protection of the present invention.
Claims
1. A composition for preparing multifunctional composite fabrics, characterized in that... Includes: composite microwave absorber and polymer matrix, The composite microwave absorber comprises a Fe3O4@TiO2@polyaniline composite, wherein the Fe3O4@TiO2@polyaniline composite has a Fe3O4 core, a TiO2 layer coating the Fe3O4 core, and polyaniline on the TiO2 layer, wherein the mass ratio of aniline to Fe3O4@TiO2 is 1:5 to 10:
1. The polymer matrix comprises poly(vinyl phosphate-hydroxyethyl acrylate-styrene), wherein the molar ratio of vinyl phosphate, hydroxyethyl acrylate, and styrene is 1 to 15:7:
1. Based on the total weight of the Fe3O4@TiO2@polyaniline composite and the poly(ethylene phosphate-hydroxyethyl acrylate-styrene) matrix, the Fe3O4@TiO2@polyaniline composite has a mass fraction of 2 to 8% by weight, and the poly(ethylene phosphate-hydroxyethyl acrylate-styrene) matrix has a mass fraction of 92 to 98% by weight.
2. A method for preparing the composition according to claim 1, characterized in that... The method includes: We offer Fe3O4@TiO2@polyaniline composites and poly(ethylene phosphate-hydroxyethyl acrylate-styrene). The Fe3O4@TiO2@polyaniline composite is brought into contact with the poly(ethylene phosphate-hydroxyethyl acrylate-styrene).
3. The method according to claim 2, wherein the mixture comprising the Fe3O4@TiO2@polyaniline composite and the poly(ethylene phosphate-hydroxyethyl acrylate-styrene) is ultrasonically stirred at room temperature for 20-50 min.
4. A multifunctional composite fabric, characterized in that... include: Basic fabric; and The composition according to claim 1 is applied to the base fabric.
5. The multifunctional composite fabric according to claim 4, wherein the base fabric is a high-temperature resistant and flame-retardant fiber fabric.
6. The multifunctional composite fabric according to claim 4, wherein the base fabric is one or more selected from polyacrylonitrile pre-oxidized yarn, phenolic fiber, polyphenylene sulfide fiber, polyimide fiber or aramid.
7. A method for preparing multifunctional composite fabrics, characterized in that... include: Prepare the basic fabric; as well as The composition according to claim 1 is applied to the base fabric by means of multiple impregnation or pad dyeing processes.
8. The method of claim 7, wherein the mass ratio of the coating formed by the composition to the base fabric is 0.5 to 1.5:
1.
9. A protective equipment, characterized in that... Includes the composition according to claim 1, or the multifunctional composite fabric according to any one of claims 4 to 6.
10. A functional component for electromagnetic shielding, flame retardancy, or weather resistance, characterized in that... Includes the composition according to claim 1.
Citation Information
Patent Citations
Textile finishing compositions
GB1268132A